2008
DOI: 10.1001/archsurg.2007.41
|View full text |Cite
|
Sign up to set email alerts
|

Hypertonic Resuscitation of Hypovolemic Shock After Blunt Trauma

Abstract: Although no significant difference in ARDS-free survival was demonstrated overall, there was benefit in the subgroup of patients requiring 10 U or more of packed red blood cells in the first 24 hours. Massive transfusion may be a better predictor of ARDS than prehospital hypotension. The use of HSD may offer maximum benefit in patients at highest risk of ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(128 citation statements)
references
References 87 publications
5
122
0
1
Order By: Relevance
“…100,[133][134][135] No pre-hospital trials concerning head-injury, conducted in the UK, could be identified. The remaining 11 studies were conducted in the USA, [136][137][138][139] (Table 25) summarising the appraisal of the four trials conducted in the UK NHS, upon which the discussion will focus, is presented below (the complete appraisal tables can be found in Appendix E (see Critical Appraisal tables). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…100,[133][134][135] No pre-hospital trials concerning head-injury, conducted in the UK, could be identified. The remaining 11 studies were conducted in the USA, [136][137][138][139] (Table 25) summarising the appraisal of the four trials conducted in the UK NHS, upon which the discussion will focus, is presented below (the complete appraisal tables can be found in Appendix E (see Critical Appraisal tables). …”
Section: Resultsmentioning
confidence: 99%
“…Five investigated interventions in head-injury, four of which fluid concerned administration 128,136,140,141 and one pre-hospital intubation. 37 The final six investigated interventions in general trauma: three fluid administration, [137][138][139] one oxygen 144 and two analgesia.…”
Section: Study Purpose and Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the increase of serum sodium and osmolality would begin to decline 0.5 or 1 h later, the impact on the immune system could last for up to 24 h after HTS administration (Bulger et al, 2008;Junger et al, 2012;Motaharinia et al, 2015). Considering the anti-inflammatory and immunosuppressive effects of MDSCs, the rise of the MDSC count induced by HTS in the early stage should be helpful in relieving inflammation damage.…”
Section: Fig 3 Variations Of Mdscs and M-mdsc/g-mdsc Ratio In Mice Bmentioning
confidence: 99%
“…Bislang konnte allerdings auch für HTS nicht belegt werden, dass damit generell die Überlebensrate verbes sert werden kann [18,26,87]. In speziel len Situationen wie akut erhöhtem Hirn druck oder schwerem Volumenmangel wurde der Einsatz von HTS dennoch er wogen [6,17,82].…”
Section: Hypertone Kochsalzlösungunclassified